Adsorbed Fibrinogen stimulates TLR-4 on monocytes and induces BMP-2 expression. (February 2017) - Oliveira, Marta I.; Pinto, Marta L.; Gonçalves, Raquel M.; Martins, M. Cristina L.; Santos, Susana G.; Barbosa, Mário A.
Graphical abstract: Abstract: Modulation of inflammatory responses to implanted biomaterials towards tissue regeneration has gained prominence as an innovative tissue engineering strategy. Recent in vitro and in vivo studies showed that Fibrinogen (Fg) adsorbed to Chitosan (Ch) substrates modulates immune cell responses, enhances the production of osteogenic factors by monocytes/macrophages and promotes bone regeneration, but the mechanisms involved remain poorly understood. Thus, the present work was conducted to clarify the molecular mechanisms of interaction between primary human monocytes and the above substrates. Cell surface expression of TLR-4 was significantly downregulated in the presence of pre-adsorbed Fg, when compared to Ch control, indicating an interaction via this receptor. The same substrate triggered MAPK activation, specifically the ERK 1/2 and JNK pathways. Importantly, both ERK 1/2 and JNK phosphorylation were reduced when TLR-4 signalling was blocked using a specific pharmacological inhibitor. Functionally, adsorbed Fg induced production of the potent osteogenic mediator BMP-2 by monocytes, while TLR-4 inhibition resulted in a significant decrease of BMP-2 mRNA and protein levels, in response to Fg stimulation. Overall, our data reveals that adsorbed Fg exerts a pro-osteogenic effect on human monocytes through its interaction with TLR-4 and subsequent production of BMP-2, elucidating two key aspects of the immunomodulatory action of adsorbed Fg in bone regeneration. Statement of Significance: Recent studies showed that when Fibrinogen (Fg) is used to modify Chitosan (Ch) substrates, it modulates the immune response, enhances production of osteogenic factors by monocytes/macrophages, and promotes bone regeneration. However, the mechanisms involved in monocyte-Fg interaction, were only partially known. Current work addresses the interaction between primary human monocytes and Ch surfaces modified by Fg adsorption (Ch-Fg) at the molecular level. Results show that monocytes interact specifically with Ch-Fg via TLR-4, triggering particular intracellular signalling pathways (ERK and JNK, but not p38), downstream of TLR-4. Functionally, Ch-Fg induced monocytes to produce the osteogenic mediator BMP-2. Thus, we clarify herein two essential aspects of the interaction between adsorbed Fg and monocytes, with impact on immunomodulation and regeneration, upon biomaterial implantation.